Global Formaldehyde Products From the Ozone Mapping and Profiler Suite (OMPS) Nadir Mappers on Suomi NPP and NOAA‐20 - Caroline R. Nowlan; Gonzalo González Abad; Hyeong‐Ahn Kwon; Zolal Ayazpour; Christopher Chan Miller; Kelly Chance; Heesung Chong; Xiong Liu; Ewan O’Sullivan; Huiqun Wang; Lei Zhu; Isabelle De Smedt; et al. (Earth and Space Science, 2023)
Abstract We describe new publicly available, multi‐year formaldehyde (HCHO) data records from the Ozone Mapping and Profiler Suite (OMPS) nadir mapper (NM) instruments on the Suomi NPP and NOAA‐20 satellites. The OMPS‐NM instruments measure backscattered UV light over the globe once per day, with spatial resolutions close to nadir of 50 × 50 km2 (OMPS/Suomi‐NPP) and 17 × 17 km2 or 12 × 17 km2 (OMPS/NOAA‐20). After a preliminary instrument line shape and wavelength calibration using on‐orbit observations, we use the backscatter measurements in a direct spectral fit of radiances, in combination with a nadir reference spectrum collected over a clean area, to determine slant columns of HCHO. The slant columns are converted to vertical columns using air mass factors (AMFs) derived through scene‐by‐scene radiative transfer calculations. Finally, a correction is applied to account for background HCHO in the reference spectrum, as well as any remaining high‐latitude biases. We investigate the consistency of the OMPS products from Suomi NPP and NOAA‐20 using long‐term monthly means over 12 geographic regions, and also compare the products with publicly available TROPOMI HCHO observations. OMPS/Suomi‐NPP and OMPS/NOAA‐20 monthly mean HCHO vertical columns are highly consistent (r = 0.98), with low proportional (2%) and offset (2 × 1014 molecules cm−2) biases. OMPS HCHO monthly means are also well‐correlated with those from TROPOMI (r = 0.92), although they are consistently 10% ± 16% larger in polluted regions (columns >8 × 1015 molecules cm−2). These differences result primarily from differences in AMFs.